2008
DOI: 10.1088/0960-1317/18/3/037004
|View full text |Cite
|
Sign up to set email alerts
|

Precision patterning of PDMS membranes and applications

Abstract: This paper presents a method for precision patterning of polydimethylsiloxane (PDMS) membranes based on parylene C lift-off. The process permits the construction of PDMS membranes either with a highly flat, uniform top surface or with a controlled curvature. Effects of varying processing parameters on the geometrical characteristics of the PDMS membranes are described. The paper also demonstrates the application of the PDMS precision patterning method to the construction of PDMS microlens arrays, which require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 17 publications
2
22
0
Order By: Relevance
“…This statement holds for measurements in both direction (parallel and perpendicular to the needles). The recovered values of the Young´s modulus of PDMS in the absence of fillers, (690 ± 10) kPa, calculated from both fits (exponential law and Mooney-Rivlin law) are coincident and in agreement with reported values in previous work [22][23][24][25]. The Young´s moduli of the composite in both directions, parallel and perpendicular to the needles are referred as E || and E  , and take values of (900 ± 10) and (780 ± 10) kPa, respectively, which corresponds to an elastic anisotropy of ca.…”
Section: 2b Elastic Propertiessupporting
confidence: 90%
“…This statement holds for measurements in both direction (parallel and perpendicular to the needles). The recovered values of the Young´s modulus of PDMS in the absence of fillers, (690 ± 10) kPa, calculated from both fits (exponential law and Mooney-Rivlin law) are coincident and in agreement with reported values in previous work [22][23][24][25]. The Young´s moduli of the composite in both directions, parallel and perpendicular to the needles are referred as E || and E  , and take values of (900 ± 10) and (780 ± 10) kPa, respectively, which corresponds to an elastic anisotropy of ca.…”
Section: 2b Elastic Propertiessupporting
confidence: 90%
“…Figure 3(b) shows arrays of 30 µm diameter openings with 100 µm, 200 µm, and 300 µm center-to-center distances all showing good results. This capability of creating holes in PDMS could not be achieved by the previously reported parylene lift-off based PDMS patterning technique since it would have been impossible to remove the parylene patterns from each of the holes by pealing them off [23]. …”
Section: Resultsmentioning
confidence: 99%
“…Eon et al demonstrated that PDMS can be directly patterned using oxygen plasma etching, but the slow etch rate (7 nm/min) due to silicon oxide-like layer formation on top and the rough surface after plasma etching is limiting its use [22]. Tong et al introduced a precision PDMS patterning method using a parylene C layer lift-off process that provided a relatively smooth surface [23]. In this method, PDMS was spin-coated and cured on a parylene C layer that was deposited and patterned by a low-pressure chemical vapor deposition and a RIE.…”
Section: Introductionmentioning
confidence: 99%
“…PDMS pre-solution was spun at 500rpm for the 30s to allow the liquid to cover the substrate uniformly and subsequently the speed was set to half of the target speed for other 30s. The final step defined as the target speed (500-6000rpm) is set for 60s to reach the desired thickness of the PDMS [21]. Four different films were prepared at four different target velocities: 500 (PDMS0.5), 1000 (PDMS1), 4000 (PDMS4) and 6000rpm (PDMS6).…”
Section: Pdms Substrates Preparationmentioning
confidence: 99%